عـــادات الخطبة والزواج عند مسلمي يوربا (نيجيريا) : دراسة فقهيّة نقدية - محب الدين، خديجة (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2015)
This study aims at analyzing the traditions of marriage among Yoruba Muslims in Nigeria, through a critical study from the perspective of Islamic jurisprudence. The research method was based on inductive analytical approach and semi-structured interviews for the collection of different opinions of classical and contemporary scholars on the concept of traditional marriage among Yoruba Muslims in Nigeria, its conditions and pillars based on the Qur'an and Sunnah. The semi-structured interviews were conducted on experienced individuals within the Yoruba community. The researcher discussed the terms connected to the traditions of marriage, its conditions, the definition of the concepts of engagement and marriage, the pillars and conditions. Thus, the research found some variances between Yoruba Muslims' traditional marriage and the Islamic jurisprudence. This is because the Yoruba Muslims have been influenced by non-Islamic traditions in which the new generation cannot differentiate between what is Islamic marriage and what is not. Based on this, the researcher recommends the revision of a few elements within Yoruba Muslims' traditions of marriage in accordance with Islamic jurisprudence to reach the expected correspondence.